STABILIZATION OF TENSION OF METAL CORD WINDING - Yu. L. Hudoley; O. M. Matveev; V. P. Domnenko (Литьë и металлургия, 2014)
Advantages of the new technology of metal cord winding on master reel which enables to reduce negative influence of this operation on straightness of metal cord, to increase quality of the reinforced rubber-cord cloth and to lower costs of car tires production are presented.